Exploring the association between hemoglobin glycation index and cognitive function in older adults with hypertension: a cross-sectional study - Hong Ding; Tingyue Kang; Wenbo Gao; Qi Wang; Shu Liu; Xiaowei Zhang; Jing Yu (BMC Geriatrics)
Abstract Background The Hemoglobin Glycation Index (HGI) quantifies the difference between the actual and expected values of glycosylated hemoglobin (HbA1c), a marker that has been closely linked to various adverse health outcomes. Nonetheless, a significant gap exists in the current literature concerning the association between HGI and cognitive function. This study aims at testing such association in older adults with hypertension, a topic that has not yet been extensively investigated. Methods A linear regression model between glycated hemoglobin A1c (HbA1c) levels and fasting plasma glucose (FPG) was constructed for the calculation of the HGI. The cross-sectional study focused on evaluating the cognitive function of hypertensive individuals (≥ 60 years old), based on the data from the 2011–2014 National Health and Nutrition Examination Survey (NHANES), by using a series of standardized tests, including the Word List Learning (CERAD-WL) and Delayed Recall (CERAD-DR) tests from the Consortium to Establish a Registry for Alzheimer’s Disease (CERAD), the Animal Fluency Test (AFT), and the Digit Symbol Substitution Test (DSST). Weighted logistic and linear regression models served for evaluating the effect of HGI on hypertensive patients’ cognitive function. Restricted cubic spline (RCS) curves assisted in detecting the underlying nonlinear associations between HGI and cognitive outcomes. Furthermore, subgroup analyses and interaction tests were performed to gain deeper insights into these associations. Results The study included 1023 participants ≥ 60 years old from 2011 to 2014 NHANES. Higher HGI was accompanied by lower DSST score (P = 0.009). In the fully adjusted model, participants in the highest quartile (Q4) of HGI possessed a lower DSST score (β = -4.50, 95% CI -8.10– -0.88) versus the lowest quartile (Q1), and were more likely to exhibit low cognitive function as evaluated by the DSST (OR = 2.21, 95% CI 0.98–5.03). According to the results from RCS analysis, HGI presented a linear relevance to cognitive function scores in older adults with hypertension. There is no interaction between HGI and the stratifying variables (sex, age, BMI, alcohol consumption, and smoking status). Conclusion High HGI was an important risk factor leading to reduced cognitive performance in hypertensive patients, ensuring HGI to be used for effectively predicting patients’ cognitive decline.